ABCG2: does resolving its structure elucidate the mechanism?. (17th December 2018) - Kapoor, Parth; Horsey, Aaron J.; Cox, Megan H.; Kerr, Ian D.
Abstract : ABCG2 is one of a few human membrane transporters which display the amazing ability to transport multiple different chemicals out of cells. These multidrug pumps, which have orthologues in all organisms, are important in humans in the context of drug pharmacokinetics, especially with respect to resistance to chemotherapy. In 2016, we presented a mini-review on ABCG2 which identified many areas of exciting research progress as well as many areas of frustrating ignorance. Just 2 years on the field has advanced, particularly with respect to structural biology as the cryo-electron microscopy revolution has brought us new insights into the structure and mechanism of ABCG2. In this update, we evaluate the degree to which new data have enhanced our understanding of the structure and mechanism of ABCG2 and whether we are now in a position to translate some of these findings into inhibitor design and development.